ICSE workshop on remote analysis and measurement of software systems (RAMSS). - Orso, Alessandro (Software engineering notes.)
The goal of this one-day workshop was to bring together researchers and practitioners interested in exploring how the characteristics of today's area of computing (e.g., high connectivity, substantial computing power for the average user, higher demand for and expectation of frequent software updates) can be leveraged to improve software quality and performance.